Determinants of tax attitude in small and medium enterprises: Evidence from Indonesia - Rosalita Rachma Agusti; Aulia Fuad Rahman (Cogent Business & Management, 2023)
This study investigates the extent to which tax literacy, power, and trust strengthen tax attitudes in Indonesian micro, small, and medium enterprises. To meet this objective, this study analyzes (1) the effect of tax literacy on trust and power, (2) the effect of trust and power on voluntary compliance and tax avoidance, and (3) the direct and indirect effects of tax literacy on voluntary compliance and tax avoidance through trust and authority. The findings indicate that tax literacy is very important in determining trust and power. Further, trust and tax authority are important to create a synergistic climate that encourages increased voluntary compliance. Despite evidence that trust in tax authorities is likely to reduce tax evasion, the power of tax authorities had no significance in determining tax evasion. In this case, power was present solely because of the tax obligations imposed through tax regulations rather than legitimacy. Additionally, this study found that trust in authority and the power of authority mediate the relationship between tax literacy and voluntary compliance. Hence, it demonstrates that voluntary compliance depends on whether or not trust and power create legitimacy in the view of taxpayers. A stronger perception of trust and power can ultimately increase tax compliance. For SMEs, the role of tax literacy is crucial, as it helps SMEs understand the facilities provided by the government in the form of tax privileges or facilities. This research uncovered the importance of tax knowledge and its benefits for SMEs in terms of understanding their situation regarding tax. Further, SMEs would be better placed to understand the privileges provided by the government if tax administration principles were simplified.
Keywords: 650; small business taxation; tax administration; tax evasion; Tax literacy; voluntary compliance